Analysis of Brand Image, Brand Trust, and Brand Awareness of Brand Loyalty for Sweetened Condensed Milk Products Frisian Flag in Surabaya City - Siti Nur Laras Ati; Reiga Ritomiea Ariescy; Supriyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The increasingly fierce competition encourages companies to spark a good brand image through goods that are aligned with the guidelines so that consumers will trust and effectively remember the brand from the experience of buying goods. This research is expected to be able to dissect the influence of brand image, brand trust, and brand awareness of sweetened condensed milk products on Frisian Flag brand loyalty in the city of Surabaya. The distribution of online questionnaires is a way of collecting data. This data collection strategy is quantitative with a sample of 119 respondents using an accidental sampling technique. The sample is composed of respondents who have purchased Frisian Flag sweetened condensed milk products at least 2 (two) times, are domiciled in the city of Surabaya and are around 17 years old. Primary and secondary data are the sources of data used. The analysis technique applied is PLS with validity test, reliability test, and hypothesis testing. From the results of the study, it can be concluded that brand image, brand trust, and brand awareness have a positive and significant effect on brand loyalty variables.